2010
DOI: 10.1029/2010gl043643
|View full text |Cite
|
Sign up to set email alerts
|

Links between a stratospheric sudden warming and thermal structures and dynamics in the high‐latitude mesosphere, lower thermosphere, and ionosphere

Abstract: [1] We analyzed neutral winds, ambipolar diffusion coefficients, and neutral temperatures observed by the Nippon/Norway Tromsø Meteor Radar (NTMR) and ion temperatures observed by the European Incoherent Scatter (EISCAT) UHF radar at Tromsø (69.6°N, 19.2°E), during a major stratospheric sudden warming (SSW) that occurred in January 2009. The zonal winds at 80-100 km height reversed approximately 10 days earlier than the zonal wind reversal in the stratosphere and the neutral temperature at 90 km decreased simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 12 publications
7
38
0
Order By: Relevance
“…The warming seen in the mesosphere/lower thermosphere around 100-120 km height at the time of the SSW onset is consistent in magnitude with the TIME-GCM/CCM 1 , GAIA 2 and HAMMONIA 3 model simulations by Liu and Roble (2002), Liu et al (2013) and Miller et al (2013), respectively, and ground-based radar (e.g. Hoffmann et al, 2007;Kurihara et al, 2010) and the MIPAS satellite observations (Funke et al, 2010).…”
Section: The Winter Arctic Middle Atmospheresupporting
confidence: 55%
See 1 more Smart Citation
“…The warming seen in the mesosphere/lower thermosphere around 100-120 km height at the time of the SSW onset is consistent in magnitude with the TIME-GCM/CCM 1 , GAIA 2 and HAMMONIA 3 model simulations by Liu and Roble (2002), Liu et al (2013) and Miller et al (2013), respectively, and ground-based radar (e.g. Hoffmann et al, 2007;Kurihara et al, 2010) and the MIPAS satellite observations (Funke et al, 2010).…”
Section: The Winter Arctic Middle Atmospheresupporting
confidence: 55%
“…A number of experimental results during the winter of 2008/2009 have shown perturbations in the neutral and ion temperature and winds (e.g. Goncharenko and Zhang, 2008;Conde and Nicholls, 2010;Funke et al, 2010;Kurihara et al, 2010), coinciding with the onset of the major stratospheric warming event of January and February 2009. Therefore the modelling efforts have been extended into the upper atmosphere to examine the dynamical coupling between middle and upper atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies describe the individual response of SSWs on the middle atmosphere regarding the dynamical and thermal structure, especially of the record warming in 2009, e.g. Manney et al (2009), Kurihara et al (2010) and Shepherd et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the major warming can be clearly identified in the MLS temperature anomalies at the stratospheric altitudes (32 km and 42 km), and temperature increases of about ∼40 K are observed. Similarly, Kurihara et al (2010) using NCEP reanalysis data showed a rapid increase of zonal temperature of about 50 K at 10 hPa pressure level over 70 • N. Such a strong temperature variability during SSWs is traditionally linked to the presence of PWs and their interactions with the circumpolar flow (e.g., Matsuno, 1971;Andrews et al, 1987). daily mean temperature shows maximum near stratopause region (between 50 and 60 km).…”
Section: Empirical Mode Decomposition (Emd)mentioning
confidence: 99%